Changes in the Expression of Aquaporin-3 in the Gastrointestinal Tract Affect Drug Absorption - Ikarashi, Nobutomo (Int J Mol Sci, 2019)
Aquaporin-3 (AQP3) plays an important role in water transport in the gastrointestinal (GI) tract. In this study, we conducted a Caco-2 cell permeability assay to examine how changes in the expression and function of AQP3 affect the rate at which a drug is absorbed via passive transport in the GI tract. When the function of AQP3 was inhibited by mercuric chloride or phloretin, there was no change in warfarin permeability. In contrast, when the expression of AQP3 protein was decreased by prostaglandin E(2) (PGE(2)) treatment, warfarin permeability increased to approximately twice the control level, and membrane fluidity increased by 15%. In addition, warfarin permeability increased to an extent comparable to that after PGE(2) treatment when cell membrane fluidity was increased by 10% via boric acid/EDTA treatment. These findings suggest the possibility that the increased drug absorption under decreased AQP3 expression was attributable to increased membrane fluidity. The results of this study demonstrate that the rate of water transport has little effect on drug absorption. However, our findings also indicate that although AQP3 and other similar transmembrane proteins do not themselves transport drugs, changes in their expression levels can cause changes in cell membrane fluidity, thus affecting drug absorption rates.